Reduction of Work Function in Nanostructured Modern Cathodes for the Field Emission (Based on the Example of Tungsten Oxide W18O49 "Nanopencils") - Strikha, M.V.; Oliynyk, I.Ye. (Physics and Chemistry of Solid State, 2025)
Within the framework of a simple analytical model, an expression has been obtained that allows to calculate the work function near the tips of a nanostructured cathodes used in modern field emission devices. Numerical evaluations performed for tungsten oxide W18O49 “nanopencils” show that taking into account the considered decrease in the surface electron gas density near the nanotip leads to a decrease in the “bulk” value of the work function ( 4.55 eV) by approximately 10%. This effect must be taken into account when calculating the emission current density according to the Fowler-Nordheim formula. It (as well as the electric field enhancement due to the tip geometry) leads to an increase in the emission current density and a decrease in the emission turn-on field.